Experiential Tourism Marketing to Create a Memorable Experience for International Tourist in Bangkok - Thein, Khin Thiri; Batra, Adarsh; Barnes, John (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study explores the role of experiential tourism marketing in creating memorable experiences for tourists in Bangkok, Thailand. The research aims to identify key components contributing to unique and memorable tourism experiences (MTEs), the influence of social media marketing, and the importance of cultural exchanges in enriching tourists' experiences. Primary data were collected using a purposive sampling technique through comprehensive in total, 20 interviews were conducted in English, at which point theoretical saturation was reached, providing insights into their perspectives on the factors that enhance their travel experiences. To analyze the qualitative data, a systematic approach involving labelling, open coding, and axial coding was used. In the labelling phase, key concepts and phrases were identified from the interview transcripts. Open coding was then applied to categorize the data into distinct themes, while axial coding helped to establish relationships between these categories. The findings highlight that tourists value eco-friendly practices, cultural immersion, and personalized experiences, all fostering deeper connections and long-lasting memories. Social media platforms, particularly Instagram and TikTok, play a significant role in shaping tourists' itineraries by providing reviews and recommendations from influencers. Additionally, there is a growing trend toward niche tourism experiences and community-based tourism that cater to individual interests. The study underscores the importance of leveraging authentic cultural engagement and user-generated content through social media to strengthen Thailand's position as a premier destination for memorable tourism.